Pomalidomide enhances the maturation of dendritic cells derived from healthy donors and multiple myeloma patients - Wang, Xi; Dai, Jingying; Xia, Jingyi; Ye, Zichen; Huang, Xiaobing; Cao, Wanjun; Xiao, Rong; He, Lin (Frontiers in Pharmacology, 2022)
Objective To explore on the effect of pomalidomide on the maturation of monocyte derived dendritic cells (moDCs) from healthy donors (HDs) and multiple myeloma (MM) patients. Methods MoDCs were generated by the incubation of monocytes from peripheral blood mononuclear cells (PBMCs) for 7 days in a medium consisting of 800U/mL GM-CSF, 500U/mL IL-4, RPMI 1640 medium, 5% human serum, 100U/mL penicillin and 0.1mg/mL streptomycin. Meanwhile, the incubation system was administrated with 10 µM pomalidomide or 1×PBS as the control group. On the 8th day, cells were harvested and analyzed by the flow cytometry. The CD80+CD86+ cell population in total cells was gated as moDCs in the FACS analyzing system. Thereafter, expression of CD40 and HLA-DR on moDCs was analyzed. Meanwhile, the supernatant from the incubation system was evaluated for the secretion of cytokines IL-12, TNF-α and MIP-1α by ELISA. Results When analyzing all the HD-derived moDCs together (n=15), pomalidomide significantly increased the mean fluorescence intensity (MFI) of CD40 expression and HLA-DR expression on moDCs compared with the control group (P=0.003, P=0.040). Meanwhile, the proportion of CD40+ moDCs and HLA-DR+ moDCs in total moDCs was significantly higher in pomalidomide group than in control group (P=0.008, P=0.032). When analyzing all MM patient-derived moDCs together (n=11), pomalidomide significantly increased the MFI of CD40 expression and HLA-DR expression on moDCs compared with the control group (P=0.047, P=0.006). Meanwhile, the proportion of HLA-DR+ moDCs in total DCs was significantly higher in pomalidomide group than in the control group (P=0.000). Moreover, HD-derived moDCs (n=8) treated with pomalidomide secreted 192% IL-12, 110% TNF-α and 112% MIP-1α of the untreated moDCs (P=0.020, P=0.006, P=0.055). However, when analyzing MM patient-derived moDCs (n=10) together, the secretion of IL-12, TNF-α and MIP-1α from moDCs showed no significant difference between pomalidomide group and the control group (P=0.458, P=0.377, P=0.248). Conclusions In vitro, 10 µM pomalidomide enhances the maturation of moDCs derived from both healthy donors and MM patients. Pomalidomide shows potential to be applied as a DC adjuvant for DC-based immunotherapy, such as DC vaccine and DC cell-therapy in MM.